Holocene glacial history of Svalbard: Status, perspectives and challenges - Farnsworth, Wesley Randall; Allaart, Lis; Ingólfsson, Ólafur; Alexanderson, Helena; Forwick, Matthias; Noormets, Riko; Retelle, Michael J.; Schomacker, Anders (Earth-Science Reviews, 2020)
We synthesize the current understanding of glacier activity on Svalbard from the end of the Late Pleistocene (12,000 yrs. before present) to the end of the Little Ice Age ( c. 1920 AD). Our glacier history is derived from the SVALHOLA database, the first compilation of Holocene geochronology for Svalbard and the surrounding waters, including over 1,800 radiocarbon, terrestrial cosmogenic nuclide and optically stimulated luminescence ages. Data have been categorized by geological setting, uniformly (re-)calibrated, quality assessed and ultimately used to constrain glacier fluctuations (deglaciation, ice free conditions, glacier re-advances and ice marginal positions). We advance existing knowledge by mapping the extent and distribution of ice-cover during the Holocene glacial maximum and the glacial minimum, as well as present retreat rates (and percentages) within Early Holocene fjord-systems. Throughout the Holocene, Svalbard glaciers have responded to a varying combination of climatic, environmental and dynamic driving factors which influence both the extent and behavior of ice margins. We discuss the complexities of glacier systems and their dynamics in response to changes in climate. This review provides a holistic state of the art of Holocene glaciers on Svalbard, suitable for orienting future works which address gaps in our current knowledge.